A comparative study of the effect of using two types of organic fertilizers(bovine- dried organic fertilizer) at different levels of eggplant growth and production /Barcelona Variety/. (Latakia University Journal -Biological Sciences Series, 2020)
The research was carried out in the agricultural season (2018-2019) in the village of Hmeimim-Jableh to study effect of organic fertilizer on the growth and production of eggplant in open field agriculture.     Eggplant hybrid "Barcelona" was used in agriculture. The study included 5 treatments in 4 replicates per treatment according to the design of the complete randomized sector     The results showed that the organic fertilization treatments achieved a significant increase in vegetative growth compared to the non-organically controlled control As the organic fertilization treatment gave (500) g / m2 organic fertilizer, the highest value of the leaf surface reached (80.82) cm2, The highest number of flowers reached (56.99)flowers/plant , and it also gave The largest number of fruit fruits reached (22.4) fruits/plant.